A conducive learning environment in international higher education: A systematic review of research on students' perspectives. (November 2022) - Xu, Xiaoming; Schönrock-Adema, J.; Jaarsma, A.D.C.; Duvivier, R.J.; Bos, N.A.
Abstract: Higher education institutions (HEIs) strive to meet international students' needs and expectations regarding their learning environments. Current literature covers a wide range of needs, expectations, and HEIs' responses. However, there doesn't seem to be a consensus about the needs and expectations to be addressed. A coherent theoretical framework may help HEIs identify areas of need and provide additional resources and comprehensive services. We performed a systematic review to obtain an overview of international students' needs, expectations, and experiences regarding their learning environments as described in the literature. We categorized students' perspectives into dimensions. Subsequently, we investigated whether these dimensions related to the three key domains outlined in the theoretical framework and the coverage of these key domains by HEIs. Sixty-three studies were eligible for inclusion. We identified 18 dimensions of international students' needs, expectations, and experiences that could be mapped onto the framework. Based on these results, the content of the three domains could be summarized as goal direction, relationships, and supporting services. Thirteen studies covered one domain, 14 covered two domains, and 36 covered three domains. To provide optimal support, HEIs should cover all three domains. Our study may help to better understand and optimize learning environments for international students. Highlights: International students' needs, expectations and experiences bear on their learning. Learning environment studies in international HE lack solid theoretical frameworks. We offer a theoretical framework to fully cover international learning environment. Key quality domains are goal direction, relationships and supporting services. 18 dimensions serve as guidelines to monitor the international learning environment.